1988
DOI: 10.2337/diacare.11.10.821
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and Prevalence of Hypertension in Diabetic Patients

Abstract: Data from several epidemiologic studies have suggested that the prevalence of hypertension in patients with diabetes mellitus is -1.5-2.0 times greater than in an appropriately matched nondiabetic population. In patients with insulin-dependent diabetes mellitus (IDDM), hypertension is generally not present at the time of diagnosis. As renal insufficiency develops, blood pressure rises and may exacerbate the progression to end-stage renal failure. In non-insulin-dependent diabetes mellitus (NIDDM), many patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
58
1
5

Year Published

1989
1989
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(68 citation statements)
references
References 46 publications
4
58
1
5
Order By: Relevance
“…These findings are in alignment with those reported in the literature where age, female gender, obesity and extensive atherosclerosis were reported as risk factors for hypertension development in T2DM patients [22].…”
Section: Discussionsupporting
confidence: 82%
“…These findings are in alignment with those reported in the literature where age, female gender, obesity and extensive atherosclerosis were reported as risk factors for hypertension development in T2DM patients [22].…”
Section: Discussionsupporting
confidence: 82%
“…Key Words: troglitazone Ⅲ blood pressure Ⅲ vasodilation Ⅲ insulin Ⅲ stress, mental E pidemiological studies have reported that diabetic persons have increased prevalence of hypertension, and the San Antonio Heart Study suggests that 85% of diabetics are hypertensive and obese by the fifth decade of their life. [1][2][3] It is also well documented that diabetic patients are prone to develop microvascular and macrovascular disease and have increased mortality. 4 -7 Although it is not clear how years of poor diabetic control lead to elevated blood pressure (BP), normalizing BP in the diabetic population is particularly important to prevent progression of diabetes mellitus (DM)-related complications.…”
mentioning
confidence: 99%
“…[1][2][3] It is also well documented that diabetic patients are prone to develop microvascular and macrovascular disease and have increased mortality. 4 -7 Although it is not clear how years of poor diabetic control lead to elevated blood pressure (BP), normalizing BP in the diabetic population is particularly important to prevent progression of diabetes mellitus (DM)-related complications.…”
mentioning
confidence: 99%
“…6 In the United States, diabetes is also the leading cause of microvascular disorders of end stage renal disease (ESRD) 7,8 and retinopathy. 9 Hypertension is 1.5 to 2.0 times more common in patients with diabetes than without diabetes, 10 and more so in females than males. 11 For example, about 40% of individuals between ages 25 to 65 already have high blood pressure (BP) at the time of diagnosis of diabetes.…”
Section: Introductionmentioning
confidence: 99%